Multipath transmission control protocol–based multi-access traffic steering solution for 5G multimedia-centric network: Design and testbed system implementation - Yoohwa Kang; Changki Kim; Donghyeok An; Hyunsoo Yoon (International Journal of Distributed Sensor Networks)
Various technologies have been developed for the efficient use of the multiple radio access technologies resource at the radio access network level or other network levels to improve user service quality in mobile communication networks. In long-term evolution, mobile carriers are commercializing radio access network-level traffic aggregation technologies such as licensed-assisted access-long-term evolution, long-term evolution-unlicensed, and long-term evolution-wireless local area network aggregation, which use the multi-accesses of the 3rd Generation Partnership Project and WiFi, and the multipath transmission control protocol–based traffic aggregation technologies at the L3 network level. The standardization of 3rd Generation Partnership Project Release 16, which is scheduled to be completed by 2020, is under progress to support the traffic aggregation technology at the L3 network level through a multi-access 5G network. Multipath transmission control protocol is also considered as a traffic aggregation technology. However, it is difficult to apply the multipath transmission control protocol employment model used in long-term evolution to the 5G network structure as it is due to the change to a common core architecture that accommodates multiple radio access technologies through one common interface. Therefore, this article proposes an optimal 5G system architecture and a multipath transmission control protocol adaptation method to support the access traffic steering function based on multipath transmission control protocol in a 3rd Generation Partnership Project 5G mobile communication network. We have verified the development of the multipath transmission control protocol–based multi-access traffic steering technology by implementing the proposed solution in a commercial server on a testbed based on the 5G system standard of 3rd Generation Partnership Project Release 15. Furthermore, this article defines problems that occur when implementing the multipath transmission control protocol–based multi-access traffic steering system and proposes relevant solutions. Based on the implementation results, it is demonstrated that the proposed multipath transmission control protocol–based multi-access traffic steering system can perform traffic steering in the 3rd Generation Partnership Project 5G network.